Recent Advances in Touch Sensors for Flexible Displays - Chenglan Ouyang; Di Liu; Ke He; Jiahao Kang (IEEE Open Journal of Nanotechnology, 2023)
A touch screen that combines a display and a touch sensor array is a critical component enabling human-machine interaction. The progress made in flexible touch screen technologies also vigorously drives the development and application of flexible electronics in various fields. Over the past decade, there have been enormous research and development efforts on new structures and materials for touch sensors in flexible displays, especially for flexible organic light-emitting diode (OLED) displays. Herein, this review discusses the mechanics and structures of flexible touch screens, including their benefits and drawbacks. The recent advances in the structures and electrode materials (e.g., ITO, silver nanowires, metal mesh, graphene, carbon nanotubes, and conductive polymers) are reviewed, and the challenges and prospects of these technologies are also explored.